Application of Artificial Intelligence in Pediatric Dentistry: A Literature Review - Noura Alessa (Wolters Kluwer Medknow Publications, 2024)
Artificial intelligence (AI) is the development of computer systems that can do tasks that normally require human intelligence. A number of dental specialties, including pediatric dentistry, now use AI and its subsets, machine learning, and deep learning. The evolution of AI in healthcare has been linked to the creation of AI applications meant to support medical professionals in diagnosing patients and choosing the best course of treatment. AI is the capability of robots to learn and use that information to carry out a range of cognitive tasks, including language processing, learning, reasoning, and making decisions-basically imitating human behavior. This review gives an overview of the numerous applications of AI that are beneficial to pediatric dentistry.